Perencanaan Desa Wisata Berbasis Pemberdayaan Ekonomi Masyarakat di Desa Sering Kecamatan Donri Donri Kabupaten Soppeng - Samsuddin Amin; Nurmaida Amri; Idawarni .; M. Yahya; Edward Syarif; Nurul Nadjmi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
Tourism Village is one of the alternative empowerment efforts through community involvement in the management of tourism potential in the village. The measure of the success of the Tourism Village program can be seen in the graph of the economic growth of the community in the village as an implication of the implementation of an empowerment-based community involvement program. The commitment of stakeholders in implementing the Tourism Village program is also the key to success. The village government, local entrepreneurs, and village communities including youth leaders, and ulama are the key words in hanging high ideals for the successful implementation of community empowerment programs in Tourism Villages. Sering Village, Donri-donri District, Soppeng Regency, topographically has a very competitive landscape to be developed into a tourism village based on natural panoramas. The main problems in this village are inadequate road infrastructure in accessing potential tourism spots, limited infrastructure and supporting facilities such as home stays and other supporting facilities. The purpose of this community service activity is to explore the potential of tourism, especially those related to the potential for natural panoramas to then be translated into tourist spots which are expected to contribute to improving the community's economy based on empowerment programs. The method of implementing the activities formulated by the Community Service Team of the Department of Architecture, Faculty of Engineering, Hasanuddin University, started from field observations followed by analysis of potential and existing problems related to the tourism village development plan at the service location. The results of the implementation of the activity showed enthusiasm, as well as a significant level of understanding and acceptance related to the design of tourism spots based on natural panoramas at the service location.